Hannah coulter eaudiobook A novel. - Berry, Wendell (Port William., 2008)
In the latest installment in Wendell Berry's long story about the citizens of Port William, Kentucky, readers learn of the Coulters' children, of the Feltners and Branches, and how survivors "live right on." "Ignorant boys, killing each other," is just about all Nathan Coulter would tell his wife about the Battle of Okinawa in the spring of 1945. Life carried on for the community of Port William, Kentucky, as some boys returned from the war while the lives of others were mourned. In her seventies, Nathan's wife, Hannah, now has time to tell of the years since the war.